Rethinking legal pluralism and Asian law in the face of globalization. Issue 3 (1st September 2016) - Kawamura, Arinori
ABSTRACT: Western law is a bundle of systematic, comprehensive rules based on, first, modern Western states' legal systems; second, constitutionalism based on liberal democracy; third, capitalist market economies based on individual freedom; fourth, the Roman law tradition; and, fifth, Christian ethics. By contrast, in many cases, non-Western law has no elaborate or solid structure based on a special mechanism, and it is not clear-cut in such a way as to clearly demark the boundary between lawfulness and unlawfulness; rather, it is flexible. Non-Western law is also referred to as customary law, and other such names. Thus, "law, " as used in the sense of non-Western law, is a cultural hybrid, and thus it is impossible to accurately understand non-Western law by using the standards for lawfulness and unlawfulness employed in the study of Western law. In this paper, I will focus on the Chinese-style of the "rule of law" through analyzing and classifying views on "rule of law" in Chinese legal academic circles and discuss the issues surrounding the "identity postulate of a legal culture" in Asian law in the face of globalization by describing the problem caused by blending Western law with non-Western law.